Body Weight Measurement in Critically Ill Patients: A Bibliometric Analysis - Refonda Rias Anggiri; Suhartini Ismail; Retnaningsih Retnaningsih; Sumardi Sumardi (Journal of Client-centered Nursing Care, 2025)
Background: Determining appropriate interventions for critically ill patients requires body weight measurement. However, researchers need specific information from scientific publications to gain a more detailed insight. Bibliometric analysis can facilitate the examination of trends in body weight measurements in critically ill patients. This study evaluates the global scientific production trend of body weight measurement in critically ill patients using network, overlay, and density visualization. Methods: The Scopus database was used to retrieve publications from 1973 to 2024. Data were saved in RIS format, processed using EndNote, and analyzed in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. We used VOSviewer software, version 6 and the RStudio package to visualize co-occurrence and co-authorship analyses, focusing on articles published, authors’ contributions, keywords, interdisciplinary areas, and countries. Results: A total of 1547 keywords were identified, with 1423 included studies. Of these, 65.5% were related to “medicine,” and 14.1% were related to “nursing.” The number of publications has increased substantially over the last 20 years. The most prolific author was Jason A Roberts., with 36 studies and 1362 citations. Keyword analysis revealed six clusters, with the most frequent keywords being “critical illness,” “hospital admission,” “body weight,” “artificial ventilation,” “intensive care unit,” and “sequential organ failure assessment.” The potential topics related to this study were issues, such as “hemorrhage,” “ground glass opacity,” “artificial feeding,” “mathematical analysis,” “blood urea nitrogen,” “net ultrafiltration,” “kidney function test,” “cross infection,” and “virus load.” The United States led globally with 457 publications, while the Middle East and Southeast Asia had lower research output. The most cited article, “Intensity of renal support in critically ill patients with acute kidney injury,” by Palevsky et al., published in 2008, garnered 1462 citations. Conclusion: This study provides a comprehensive bibliometric overview, offering valuable insights for future research on body weight measurement in critically ill patients.